1987
DOI: 10.1002/1097-0142(19870915)60:6<1263::aid-cncr2820600617>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Type IV collagenase activity of a primary HSV-2-induced hamster fibrosarcoma and itsin vivo metastases andin vitro clones

Abstract: The expression of a basement membrane (BM) collagen-degrading metalloprotease (Type IV collagenase) was studied in a herpes simplex virus (HSV)-2 transformed hamster fibrosarcoma and its in vivo derived sublines and in vitro derived clones of varying metastatic potential. The primary parent tumor was shown to release more or less Type IV collagenolytic activity compared with its sublines (derived from lung nodules that developed after resection of the primary tumor). Normal baby hamster kidney and hamster embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Among the enzymes regulated by second messengers are metalloproteinases (Angel et al, 1987;Brinckerhoff et al, 1986;Frisch et al, 1987;Matrisian et al, 19861, which are necessary for active cellular movement (Buckley, 1988) and metastasis (see reviews, Fidler, 1990;Liotta et al, 1986;Weiss, 1986). Since type IV collagen is an important structural component of basement membranes, a major barrier to tumor cell invasion, it is not surprising that type IV collagenolytic (gelatinase) activity correlates with metastatic potential and with in vitro invasive potential in a variety of human and rodent tumors (Bernhard et al, 1990, Brown et al, 1990, Liotta et al, 1980Hendrix et al, 1990;Khokha et al, 1989;Mignatti et al, 1986;Moll et al, 1990;NakaJima et al, 1987;Stetler-Stevenson, 1989, 'Ihkajima et al, 1987Teale et al, 1987;Zucker et al, 1990). For the cell lines examined in this study, there is a direct correlation between levels of type IV collagenase mRNA and invasive and metastatic potential (Welch et al, 1991) and between mRNA levels and protein levels of type IV colla- genase (Hendrix et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Among the enzymes regulated by second messengers are metalloproteinases (Angel et al, 1987;Brinckerhoff et al, 1986;Frisch et al, 1987;Matrisian et al, 19861, which are necessary for active cellular movement (Buckley, 1988) and metastasis (see reviews, Fidler, 1990;Liotta et al, 1986;Weiss, 1986). Since type IV collagen is an important structural component of basement membranes, a major barrier to tumor cell invasion, it is not surprising that type IV collagenolytic (gelatinase) activity correlates with metastatic potential and with in vitro invasive potential in a variety of human and rodent tumors (Bernhard et al, 1990, Brown et al, 1990, Liotta et al, 1980Hendrix et al, 1990;Khokha et al, 1989;Mignatti et al, 1986;Moll et al, 1990;NakaJima et al, 1987;Stetler-Stevenson, 1989, 'Ihkajima et al, 1987Teale et al, 1987;Zucker et al, 1990). For the cell lines examined in this study, there is a direct correlation between levels of type IV collagenase mRNA and invasive and metastatic potential (Welch et al, 1991) and between mRNA levels and protein levels of type IV colla- genase (Hendrix et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have attempted to correlate the invasive and metastatic properties of cancer cells in experimental models with various biological properties of cells that can be quantitated in vitro (Garbisa et al, 1987; Liotta and Stetler- Stevenson, 1989). Most of these studies reported a close correlation between metastasis and increased type-IV collagenaseigelatinase secretion by cancer cells; other reports, however, using different experimental models, failed to find such correlations (Noel et al, 1991;Teale et al, 1987). Increased levels of type-1V collagenase in malignant as compared with normal or benign tissues have been demonstrated by immunohistochemical (Monteagudo et a/., 1990) and tumor-extraction procedures (Tsuboi et al, 1988).…”
Section: Discussionmentioning
confidence: 99%